The living Paul : an introduction to the Apostle's life and thought - Thiselton, Anthony C. (Downers Grove, Ill. : IVP Academic, 2009)
The apostle Paul has long had his admirers and revilers. And contemporary Christians often harbor private misgivings about this prominent apostle. Paul sounds harsh, intolerant, misogynistic, and his gospel surely misconstrues the message of Jesus. "How is it," they want to ask, "that some Christians can speak so fondly of Paul?" Anthony Thiselton is an unabashed admirer of Paul, a student of his letters and a devotee of his gospel. Over a range of issues, Thiselton cleans the lens and sharpens the focus to give us snapshots of Paul's life, mission and thought. --from publisher description.
A first obstacle to appreciating Paul : Paul and Jesus -- A second obstacle to appreciating Paul : an 'immense cut'--new creation -- Apostle to the Gentiles (1) : traveller and missionary-pastor -- Apostle to the Gentiles (2) : traveller, pastor, letter-writer -- Jesus Christ in Paul -- Paul's view of God and its Trinitarian implications -- Paul's view of the Holy Spirit -- Paul's view of humanity -- Human alienation and Paul on sin -- The work of Christ and being 'in Christ' -- Justification and the law -- Why the church? -- The ministry of the word -- Baptism and the Lord's Supper or Eucharist -- Paul's ethics and views on Christian lifestyle -- Cosmic and human destiny and the present : resurrection, judgment, and the Parousia -- Paul and postmodernity.
Includes bibliographical references (p. 163-174) and indexes.
Keywords: Paul, -- the Apostle, Saint; Bible. -- Criticism, interpretation, etc